POLICY ANALYSIS AND IMPLEMENTATIONBUILDING CONSTRUCTION APPROVAL (PBG) IN SUPPORTING REGIONAL DEVELOPMENT IN MEDAN CITY - Rizki Irawan; Cut Nuraini; Ruth Riah Ate Tarigan (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to analyze the role of Building Construction Approval (PBG) in supporting regional development in Medan City. PBG as a regulatory instrument for building construction in Medan City plays an important role in ensuring orderly, safe, and sustainable development. This study uses a qualitative approach with data collection techniques through interviews, documentation studies, and observations. The results of the study indicate that although PBG makes a significant contribution to the regulation and supervision of development, there are challenges in its implementation, such as limited resources, developer non-compliance, and the complexity of licensing procedures. The recommendations produced include simplifying the licensing process, increasing human resource capacity, stricter law enforcement, and the use of technology for more effective monitoring. With the increased effectiveness of PBG, it is expected to support the development of the Medan City area to be more orderly, safe, and sustainable.